A Wireless Body Area Network of Intelligent Sensors for Biomedical Applications: Design and Performance Analysis - Hamdi, Abdelaziz; Nahali, Amina; Braham, Rafik (Joint IFIP Wireless and Mobile Networking Conference (Online), 2022)
Wireless body area networks, a branch of wireless sensor networks, are a still-emerging sector of biomedical technology. The wireless body area network has widely appeared after the development of wireless sensor networks which reached some level of maturity. Recently, this field has gained significant attention due to its applications which mainly are toward biomedical and healthcare applications. Nowadays, small sensors that can transfer data to other devices can now be implemented anywhere on the human body to record different physiological indicators and enable further actions to be conducted, such as processing, remote procedures and aiding decision. Considering this recent hot subject, the intent of this work is to present a new approach of the design and the performance analysis of Wireless body area network, specifically channel modeling between wearable wireless sensors. The behavior of these sensors on the human-body is theoretically and experimentally explored in detail along this paper. A good agreement is obtained between the theoretical and the experimental results despite the complexity of the physiological behavior of human body.